If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6 + 5x = 57 Reorder the terms: -6 + 4x + 5x = 57 Combine like terms: 4x + 5x = 9x -6 + 9x = 57 Solving -6 + 9x = 57 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 9x = 57 + 6 Combine like terms: -6 + 6 = 0 0 + 9x = 57 + 6 9x = 57 + 6 Combine like terms: 57 + 6 = 63 9x = 63 Divide each side by '9'. x = 7 Simplifying x = 7
| 9=3g | | 180=16x-3+45 | | 5x+1-2x=27 | | 0.75y=2x-6 | | 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form | | -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 | | 3(c-63)=27 | | 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 | | 4x+10-2x=-10 | | 3(k+9)=72 | | -t+-6=-10 | | 32(x-1)+115x+10(x+2)=1607 | | -24=8(r+63) | | 43=2x+2x+7 | | 3/7x3 | | 3h+2=-4 | | -2x-2+5x=16 |